Desenvolvimento de uma metodologia em fluxo para especiação redox de As em águas utilizando Espectrometria de Absorção Atômica com Geração de Hidretos - Silva, Adriana Cósmem da (2000)
A method was developed for determination of arsenic by Atomic Absorption Spectrometry - Hydride Generation in Flow Injection Analysis (FIA). The flow injection system was operated in the merging zones configuration, where sample and reagent are simultaneously injected into two carrier streams, HC1 and H2O, respectively. For separation of arsine a continuous gas-liquid separator was designed. The liquid phase flows to a free-running drain while the gaseous phase is purged by nitrogen into the atomization cell. The optimum conditions for the generation of arsine were established as: reaction coil of 50 cm, sample and reagent injected volume of 250 p.L, 1.0% (m/v) solution of sodium tetrahydroborate and 1.0 mol L’1 hydrochloric acid, cell temperature of 900°C, flow rates of 3.6 mL min’1 for hydrochloric acid and tetrahydroborate Solutions and a flow rate of 130 mL min-1 for the carrier gas (N2). Many elements cause interferences in this technique in gaseous and condensed phases. It was found that Mn(II), Pb(Il), Fe(IIl), Cu(II), Ni (II), Zn (II), Al (III) and Cd (II) caused signal reductions for arsenic of at least 10%. The interferences were reduced by using an on-line mini-column with 50 mg of the cation exchange resin Amberlite IRA-120. The interferences in the gaseous phase were caused by Se(IV), Sn(II), Sb(III), Bi(III) and Te (IV). To overcome these efíects, thioureia was used as masking agent. Under the optimum experimental conditions, the detection limit. defined as three times the standard deviation of the blank measurement, was found to be 0,35 ng mL’1 for As(lII) and 0,52 ng mL’1 for As(V). The relative standard deviation of 2,3% for 0,1 mg L’1 As(IIl) and 1,7% for 0,1 mg L’1 As(V) and a sampling rate of about 120 determinations per hour. The method was shown to be satisfactory for determination of traces arsenic in water samples (natural and certificate).